The Poet’s Mask, the Ballad Tradition of Villon and Leftism in Central European Poetry of the 1930s - Száz, Pál (Anafora, 2024)
The study deals with poetry collections, two Hungarian, one Czech and one Croatian, which were written in the second half of the thirties of the 20th century. The considered collections of György Faludy, János Erdődy, Vítězslav Nezval and Miroslav Krleža pose the problem of authorship, represent masked poetry, construct other people’s roles (Villon, Petrica Kerempuh) and use a pseudonym (Robert David). The aforementioned four collections are also interesting from the point of view of the Central European reception of Villon and the genre tradition of the French ballad with which they are directly or indirectly connected. From the point of view of left-wing political poetry, the collections can also be considered top productions. In the case of researching the relationship between the authors and their masks, it is inevitable to analyze the poetic appearance of apostrophes and the phenomenalization of poetic voices.